(untitled) (Revista Iberoamericana de Estudios Municipales, 2021)
The article analyzes Oaxaca de Juárez, San Juan Bautista Tuxtepec and Salina Cruz, municipalities of the state of Oaxaca, Mexico, during the period 2008-2019, with the aim of knowing the relationship between crime incidence and the subsidy for municipal security. It uses a quantitative methodology through the design of a database with documented information from government institutions. The hypothesis proposed is that the security subsidy has a positive and significant impact on reducing the crime incidence of the study municipalities. For its verification, descriptive statistics and regression methods are applied, obtaining a high positive association between the analyzed variables. Representing valuable information for the design of public policies for public safety.